A scoping review on early inflammatory bowel disease: definitions, pathogenesis, and impact on clinical outcomes. (December 2022) - Estevinho, Maria Manuela; Leão Moreira, Paula; Silva, Isabel; Laranjeira Correia, João; Santiago, Mafalda; Magro, Fernando
Background: Crohn's disease (CD) and ulcerative colitis (UC) arise from a dysregulation of the balance between commensal microbiota and mucosal-associated immune system, in patients with genetic and environmental predisposition. Different pathophysiological mechanisms have been reported to influence disease history, with impact on disease phenotype and risk of complications. Objectives: This review aims to summarize the definitions of early CD and UC, analyze the underlying immunological mechanisms, and evaluate the impact of recognizing and treating early inflammatory bowel disease (IBD) on patients' prognosis (short- and long-term outcomes). Design: To address this issue, we have performed a scoping review. Data sources and methods: Three online databases (MEDLINE, Web of Science, and ScienceDirect) were searched and the results were independently screened by two reviewers. Results: From 683 records identified, 42 manuscripts evaluating early IBD in adult patients were included. The 'early CD' concept was first described in 2008. Four years later, an international consensus proposed the definition of diagnosis up to 18 months, in patients without previous or current need for disease-modifying therapies. Several other definitions have been proposed; the '2 years since diagnosis' is the most used, regardless of disease characteristics or medication. The amount of evidence on early UC is lower and more recent. Regarding early disease pathogenesis, most theories emphasize the prominent role of innate immunity, followed by early-Th1 adaptive response. Conclusion: The treatment of early CD seems to be crucial for the management of CD patients, impacting short-, medium-, and long-term outcomes. On the other hand, the early treatment of UC appears to be less advantageous, yet evidence comes from only a few retrospective studies.